The effect of growth regulators on ascorbic acid and solubre carbohydrates contents of strawberry fruit (Fragaria Hybridus) - Gutierrez, Luiz Eduardo; Castro, Paulo R. C.; Minami, Keigo; Cesar Junior, Wilson P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
Several growth regulators were sprayed on strawberry plants: SADH (5000 ppm), CCC (2000 ppm), IAA (10 ppm, 3 times), GA 10 ppm, 3 times) and GA (550 ppm), Ascorbic acid, dry weight and soluble carbohydrates contents of fruits were determined. Statistically differences were not observed between treatments and control. Dry weight varied from 7.62 to 9.53%. Ascorbic acid content varied from 35.88 to 71.81 mg/100 g on fresh weight basis. Mean values of soluble carbohydrates, in grams/100 g on fresh weight basis, were total (5.58), sucrose (1.01), glucose (1.63) and frutose (1.54).